2013
DOI: 10.11607/jop.1057
|View full text |Cite
|
Sign up to set email alerts
|

Family and School Environmental Predictors of Sleep Bruxism in Children

Abstract: The present investigation suggested that, among family and school-related matters, having divorced parents and not falling asleep easily were two predictors, even if weak, of a child's self-report of SB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 0 publications
2
14
0
10
Order By: Relevance
“…Indeed, the literature is supportive of the relationships between SB and behavioural health issues as well as between bullying and psychological disorders. A study on Dutch adolescents showed an association of SB with stress and depressive mood , in line with the findings on Israeli adolescents that found an association with feeling stressed . In addition, another Israeli study reported an association between depression and suicidal tendencies in adolescents with bullying behaviours .…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, the literature is supportive of the relationships between SB and behavioural health issues as well as between bullying and psychological disorders. A study on Dutch adolescents showed an association of SB with stress and depressive mood , in line with the findings on Israeli adolescents that found an association with feeling stressed . In addition, another Israeli study reported an association between depression and suicidal tendencies in adolescents with bullying behaviours .…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, changes in lifestyle of a patient may affect the frequency, duration and severity of bruxism. 8 Based on the child's history, emotional stress associated with change of school could have increased the severity of both NE and bruxism in the last month. In addition, her habit was aggravated by flu and common cold.…”
Section: Discussionmentioning
confidence: 99%
“…Its occurrence has been attributed to genetic, psychological, behavioral, environmental, systemic, and local causes. [5][6][7][8][9][10][11] In a recent study, the C allele carrier of HTR2A single-nucleotide gene polymorphism was significantly associated with an increased risk of SB. 5 Psychological and behavioral factors include anxiety, stress and individual personality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 However, we are unaware of any systematic analysis of published studies that addressed SB in children and adolescents, even though several published studies have suggested a possible association between psychosocial factors and bruxism in both children [8][9][10][11][12][13][14][15][16][17] and adolescents. 2 However, we are unaware of any systematic analysis of published studies that addressed SB in children and adolescents, even though several published studies have suggested a possible association between psychosocial factors and bruxism in both children [8][9][10][11][12][13][14][15][16][17] and adolescents.…”
Section: Clinical Pediatricsmentioning
confidence: 99%